Estudo Fitoquímico e Biológico de Hymenaea courbaril L. - Aguiar, José Cláudio Dias (2009)
The phytochemical study of Hymenaea courbaril L., named “jatobá”, was executed by fruit`s bark of this vegetal, that is applied in inflammatory and intestinal diseases. Essential oil was extracted from mature fruit and 76,17% of the constituents were identified. The major constituent was -copaene. The composition of this oil was compared with the composition of the oil obtained on immature fruit, whose 93,34% of the constituents were identified. The major constituent of immature fruit was germacrene-D. Sesquiterpenes were present into both oils. The study of the fixe constituents permitted to isolate two ent-labdanic diterpenes, zanzibaric acid and isoozic acid, and the sesquiterpene caryolane-1,9-diol, that was a inedited substance in Hymenaea species. The biological study revealed that essential oils of mature fruit and immature fruit were satisfactory larvicidal agentes about Aedes aegypti and their LC50 14,85 ± 0,44 ppm and 28,44 ± 0,27 ppm, respective. A satisfactory antioxidant activity about DPPH free radicals was verified for extract in methanol whose IC50 0,04 mg/mL. The extract in ethyl acetate showed notable allelopathic effect on Lactuca sativa L., and hypocotyls growth was reduced in 44,68% (in concentration 0,4 mg/mL) and radicules growth was reduced in 31,47% (in concentration 0,8 mg/mL).